The unique antimicrobial peptide repertoire of stick insects. (February 2020) - Shelomi, Matan; Jacobs, Chris; Vilcinskas, Andreas; Vogel, Heiko
Abstract: The comparative analysis of innate immunity across different insect taxa has revealed unanticipated evolutionary plasticity, providing intriguing examples of immunity-related effector gene expansion and loss. Phasmatodea, the stick and leaf insects, is an order of hemimetabolous insects that can provide insight into ancestral innate immunity genes lost by later insect clades. We injected the stick insect Peruphasma schultei with a mixture of microbial elicitors to activate a strong immune response, followed by RNA-Seq analysis to screen for induced immunity-related effector genes. This revealed a highly diverse spectrum of antimicrobial peptides (AMPs) belonging to the attacin, coleoptericin, defensin, thaumatin, and tachystatin families. In addition, we identified a large group of short, cysteine-rich putative AMPs, some of which were strongly elicited. The immunity-related effector gene repertoire also included c-type and i-type lysozymes and several pattern-recognition proteins, such as proteins that recognize Gram-negative bacteria and peptidoglycans. Finally, we identified 45 hemolymph lipopolysaccharide-binding protein sequences, an unusually large number for insects . Taken together, our results indicate that at least some phasmids synthesize a broad spectrum of diverse AMPs that deserve further in-depth analysis. Highlights: The stick insect Peruphasma schultei has a strong immune response to microbial challenges. Phasmatodea have a greater diversity of antimicrobial peptides than related insects. These include attacins, coleoptericins, defensins, thaumatins, and tachystatins. They express a large number of hemolymph lipopolysaccharide-binding proteins .